(3HZjI GdWGdHjf dHjGf GdeTGjN GdeYJeOjf Ch GdeMbbjfs - (3CMeO Hf eMeO Hf CMeO Hf Ydj GdTgjQ HGdfNdi Gdecj GdTGaYj,J (B1130 (3g` s ((3Ydi Hf SYO GdHjhSi GdeYdha GdTGaYi s)
(3ChdgG (B:s
(3GdMeO ddg GdPi YR LdGdg adG JOQcg GdCagGe s
(3BNQgG (B:s
(3CHjGJ ef GdTYQ eWdYgG jGfGXQkG ajeG YeOJ HLeYg CYPQ aEf CNGd GdHUjQI jYPQ s
(3Ydi GdhQbI GdChdi cJGHI ef GdSjO eQJVi GdRHjOi TGQM GdbGehS JGQjNgG (B1197 (3jLjR HgG GdTjN Ydi Hf SYO GdHjhSi hjQhi ajgG SfOg GdeJUd HGdeDdas
(3Ke ELGRGJ hbQGAGJ dHYV GdYdeGAs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B245 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B1 - (3U (B173s
(3HQhcdeGf edMb (B- (3GdLRA (B2 - (3U (B520 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B1 - (3U (B47 s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJGQjNs